Partisipasi Petani Padi Sawah dalam Pengendalian Hama Penyakit Secara Ramah Lingkungan di Kecamatan Balubur Limbangan Kabupaten Garut - Indania Pramaulidia; Dedy Kusnadi (Politeknik Pembangunan Pertanian Bogor, 2020)
The application of pest disesase control according to the recommendation in Balubur Limbangan has only been implemented around 47.1%, so that most of the farmers participation is still low and the conditions of farmers in the field are still using chemical pesticides. Therefore the importance of environmental friendly pest control. This research was aimed at paddy rice farmers in Balubur Limbangan, especially in the Dunguswiru Villages, Surabaya and Ciwangi. Each village is represented by one group of farmers, then selected based on certain criteria. Next determination the sample using the Slovin formula combined with Rubin'sÂ and Luck theory so that the total is 50 respondents. Then to using the Simple Random Sampling technique. The results showed the participation of rice farmers was low category. Then the factors of farmer participation in internal factors are education (implementation and evaluation), while external factors are extension activities, availability of information, support from farmer groups, and availability of infrastructure (planning and implementation aspects). Meanwhile, the lowest indicator that becomes the problem priority is the cultural pest control so it is used as counseling material.